\(μ-e\) conversion in a model of electroweak scale right-handed neutrino mass - Dinh, Dinh Nguyen; Thi Man, Duong; Thi Nhuan, Nguyen (Communications in Physics, 2023)
We perform a detailed analysis of the \(μ-e\) conversion within an extended version of the standard model (SM) with mirror symmetry and low energy of the electroweak scale of the type I seesaw neutrino mass generation. After a brief introduction to the model, we derive the \(μ-e\) conversing ratio at one-loop approximation, in which the running inside are W gauge boson or singly charged scalars accompanying with neutrinos, and neutral scalars with new leptons. We focus, mainly, on predictions of observable possibilities and constraints set on relevant couplings from the \(μ-e\) conversion in nuclei.